1999
DOI: 10.1023/a:1008317906069
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This article discusses the growth of methanotrophic biofilms. Several independent biofilm growths scenarios involving different inocula were examined. Biofilm growth, substrate removal and product formation were monitored throughout the experiments. Based on the oxygen consumption it was concluded that heterotrophs and nitrifiers co-existed with methanotrophs in the biofilm. Heterotrophic biomass grew on soluble polymers formed by the hydrolysis of dead biomass entrapped in the biofilm. Nitrifier populations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 31 publications
3
9
1
Order By: Relevance
“…As shown in Figure 2 a, the highest specific growth rate was reached in the NMS sets of the conventional system, which can be associated with the dominance of fast-growing type I methanotrophs in the biomass due to the absence of the competitive inhibition caused by ammonia [ 33 ]. The growth rate of mesophilic methanotrophs reported in the literature depends on the type of bacterial strain present in the culture media and has a wide range of 0.02 to 0.2 h −1 , which is an accordance with the values obtained in this study [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 2 a, the highest specific growth rate was reached in the NMS sets of the conventional system, which can be associated with the dominance of fast-growing type I methanotrophs in the biomass due to the absence of the competitive inhibition caused by ammonia [ 33 ]. The growth rate of mesophilic methanotrophs reported in the literature depends on the type of bacterial strain present in the culture media and has a wide range of 0.02 to 0.2 h −1 , which is an accordance with the values obtained in this study [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
“…Figure 4 illustrates the relationship between the growth rate and the methane uptake rate in terms of yield. In the growth phase, the biomass yield for the four sets were comparable and ranged between 0.5 and 0.6 mg VSS/mg CH 4 , which is in accordance with the values reported in the literature for methanotrophic bacteria of around 0.4 to 0.6 mg VSS/mg CH 4 [34,38,39]. On a similar note, the biomass yield in the growth phase was substantially higher than the PHB accumulation phase due to the low growth rate in the accumulation phase compared to the relatively high methane uptake rate.…”
Section: Methane Uptake and Biomass Yieldsupporting
confidence: 90%
“…The observed yield represents the combination of cellular yield from methanotrophic and cyanobacterial growth. Literature values of methanotrophic yields relevant for our study have been reported by Leak & Dalton (1986) and Arcangeli & Arvin, (1999) . By theoretical analysis and experimental observations on suspended Methylococcus capsulatus, Leak & Dalton (1986) reported cellular yield of 0.6-0.7 g VSS∙g CH 4 −1 on cultivation conditions similar to this study.…”
Section: Resultsmentioning
confidence: 98%
“…Surface-water runoff can bring additional inputs of nitrogen and phosphorus from fertilisers as well as suspended sediment to an estuary (Logan and Cebulski 1970;Balls 1994). Groundwater always has higher concentrations of nutrients and ions than does the surface water, either from anthropogenic sources (Johannes and Hearn 1985;Valiela et al 1999;Slomp and Van Cappellen 2004) or from subsurface biogeochemical reactions (Moore 1999). Quantification of the relative inputs of nutrients from different water sources into hypersaline estuaries would be greatly enhanced by improved capacity to distinguish between those sources.…”
Section: Introductionmentioning
confidence: 99%